The use of metaheuristics models in Industrial Logistics. The case of vehicle routing - Cachay Boza, Orestes (2012)
The Vehicle Routing Problem considers the design of sets of minimal cost routes, from an originated point knowned as deposit to an ended point. In this problematic situation, a key element in delivery systems is the sequencing of transport units, determined by the requirement of customers. The aim of this article is to present a new method of solving the problem of allocation of routing companies with the need to distribute products, through new models that use different algorithms. The model designed from the analysis of a set of metaheuristics, develop viable options to solve the daily problem of how to allocate and distribute products, from the company to customers, with efficiently and effectively ways.